Teacher evaluation by different internal evaluators: Head of departments, teachers themselves, peers and students - Talal S. Almutairi; Nawaf S. Shraid (International Journal of Evaluation and Research in Education (IJERE), 2021)
This study analyzed teacher evaluation in school, through involving different internal evaluators, in order to determine the extent to which they evaluate teacher performance accurately and objectively. Evaluation survey instruments are used in this study, which are designed based the criteria of existing teacher evaluation system in the context, along with other criteria for evaluating teachers. The sample of this study included teachers, heads of departments and students from high schools in four different districts in Kuwait, received responses as 100 from heads of department, 100 from teachers ‘self-evaluation’, 100 from peer and 912 from students. The findings show that there is no significant difference between teachers’ self-evaluation and heads of departments’ evaluation. On the other hand, this study finds that subjectivism and competition may have an effect on peer evaluation and students may over-evaluate their teachers’ performance as attempt to draw a better picture of their teachers in front of evaluators.